Tentang Ide Reformasi Dalam Islam - Faimau, Gabriel (Perspektif, 2009)
Does Islam need a reformation? Does Islam need to go through a period of enlightenment? These questions are two common questions in the modern studies of Islam and Muslim societies, particularly in the contemporary Western academic world. Interestingly, the history of Christianity is often cited as a point of reference or a point of departure in the discussions of such questions. Christian or Western framework is therefore unavoidably used to frame the history and progress in Islam. What has often been neglected is the fact that Muslim societies in fact have gone through their own particular cycle of reformation or renewal. Drawing upon the observation of Ibnu Khaldun (1332-1406), a notable Arabic historian, on the renewal cycle within Muslim societies six hundred years ago, this article discusses in a simple way the idea of reformation in Islam.